Health information behavior research with marginalized populations. Issue 1 (24th October 2017) - Hawkins, Blake; Costello, Kaitlin; Veinot, Tiffany; Gibson, Amelia; Greyson, Devon
ABSTRACT: As part of an increasingly vibrant area of research, information behavior scholars have shown that traditionally marginalized populations (e.g., older adults, LGBTQ people, people of color, low‐income people and people with chronic diseases or disabilities) may have distinct health information needs and information behaviors. These differences may arise from unique patterns in marginalized groups' life experiences, health risks and burdens, social networks and available resources, as well as dynamics of social marginalization and exclusionary service design. This subfield of information studies challenges established notions of health information‐seeking behaviours to further develop theories and models, as well as propose new models for information services and technologies. The unique characteristics of marginalized populations have necessitated the development of novel research approaches and methods, as well as interdisciplinary collaborations and community‐based partnerships. This panel invites audience members to think critically about what it means to engage marginalized populations in research and the methods and approaches needed to do so in a health context. It will also allow participants to broaden their understanding about the health information‐seeking behaviors of marginalized populations. Panelists will introduce and contextualize marginalized populations' health information‐seeking behaviours and explore potential or existing connections between themes from a variety of disciplines. Following a brief introduction and presentations from five panelists (who are themselves exploring marginalized populations' health information‐seeking behaviours), there will be an open discussion session with the audience in a World Café format.